Rumah Ideal Dalam Al-Qur’an (Kajian Tafsir Tematik) - Lailatul Rif’ah; Yulistiani (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research will reveal what are the criteria for an ideal home in the Al-Qur'an. To make it easier to explain understanding and what are the criteria for an ideal home in the Qur'an, use Abdul Hay Al-Farmawi's perspective thematic interpretation approach, namely a thematic analysis method that reviews a detailed theme like the Maudhu'i method and leaves the theme alone. is reviewed in detail based on information from the verses of the Koran. By using Abdul Hay Al-Farmawi's thematic perspective approach, it is hoped that we can find out what the criteria for an ideal house are in the Al-Qur'an. considering that the role of the house is very important for human survival, especially Muslim families. In the Qur'an the terms al-Bayt are mentioned 51 times, al-Dar 52 times, al-maskan 67 times, al-manzil 20 times, al-Ma'wa 22 times, al-Mustaqarrun 20 times. 38 times. The criteria for an ideal house are: a house that is clean and can be used for worship, a house that is safe and provides peace, a house that has plants in the yard, and a house that provides a sense of comfort by channeling love towards each other.